2004
DOI: 10.1002/polb.20014
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray photoelectron spectroscopy of miscible poly(methyl methacrylate)/poly(styrene‐co‐acrylonitrile) and immiscible poly(methyl methacrylate)/polyacrylonitrile polymer surfaces metallized by nickel

Abstract: A miscible blend of poly(methyl methacrylate) and poly(styrene-co-acrylonitrile) and an immiscible blend of poly(methyl methacrylate) and polyacrylonitrile were metallized by nickel, and their surfaces were analyzed by X-ray photoelectron spectroscopy. Before metallization, the heteroatom distribution at the polymer surface was very different in the miscible and immiscible blends. However, this distribution was modified during metallization, which was only possible via polymer-bond breaking, leading to similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is reported to be a highly sensitive surface analysis technique which probes the top 10 nm of a polymeric film, and specifically useful for analysing the elemental composition and chemical-bonding state of the surface [324,325]. A number of studies have reported the XPS studies of PSt and PAN homopolymers, and their copolymer thin films [325][326][327][328][329][330][331][332]. In this study, the surface composition of the PSt and PAN homopolymers, and different compositions of St-AN statistical, block and gradient copolymer thin films have been studied using a Kratos AXIS Ultra XPS.…”
Section: Preparation Of Thin Films Of St-an Copolymersmentioning
confidence: 99%
“…It is reported to be a highly sensitive surface analysis technique which probes the top 10 nm of a polymeric film, and specifically useful for analysing the elemental composition and chemical-bonding state of the surface [324,325]. A number of studies have reported the XPS studies of PSt and PAN homopolymers, and their copolymer thin films [325][326][327][328][329][330][331][332]. In this study, the surface composition of the PSt and PAN homopolymers, and different compositions of St-AN statistical, block and gradient copolymer thin films have been studied using a Kratos AXIS Ultra XPS.…”
Section: Preparation Of Thin Films Of St-an Copolymersmentioning
confidence: 99%